Building a career: gender and employment in a male-dominated profession - Caven, Valerie. (1999)
Models of employment have become gendered with the 'standard' or masculine model following an unbroken, linear career path whilst the feminine model comprises periods of both full-time and part-time employment as well as intervals of non-participation in the labour market. Commitment to work is defined against these norms with those women who follow the masculine career pattern being said to display greater commitment to work than those who follow an alternative path. It is considered that career progression within an organisational hierarchy is dependent upon following the ‘standard' type of career path, which disadvantages women as historically they have been less likely than men to follow such a path.